A century of environmental legislation - Louis P. Cain; Brooks A. Kaiser (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2015)
We find three intertwined ambitions that drove federal legislation over wildlife and biodiversity at the beginning of the 20th Century: establishment of multiple-use federal lands, the economic development of natural resources, and the maintenance of option values. We examine this federal intervention in natural resource use by analyzing roll-call votes over the past century. These votes involved decisions regarding public land that reallocated the returns to users by changing the asset's physical character or its usage rights. We suggest that long term consequences affecting current resource allocations arose from disparities between broadly dispersed benefits and locally concentrated socio-economic and geophysical (spatial) costs. We show that a primary intent of public land management has become to preserve multiple-use option values and identify important factors in computing those option values. We do this by demonstrating how the willingness to forego current benefits for future ones depends on the community's resource endowments. These endowments are defined not only in terms of users' current wealth accumulation but also from their expected ability to extract utility from natural resources over time.
Keywords: N51; N52; Q28; Q23; Q24; 330; Environmental Legislation; Wildlife Legislation; Endangered Species Act; Lacey Act; Economic History of the Environment